Labor Dispute Mediation: A Constitutional Perspective to Realize Social Justice in the 1945 Constitution - Riana, Ana; Enrico Winadi; Riski Eka Purnairawan (As-Siyasi: Journal of Constitutional Law, 2026)
This study aims to analyze labor dispute mediation as a constitutional vehicle for realizing social justice, not merely an administrative instrument. The urgency of this study departs from the fact that the settlement of labor disputes through mediation in Indonesia has so far been more emphasized on procedural efficiency and technical neutrality, without considering the structural inequality between workers and employers, so that substantive justice as mandated by the Preamble and Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia is often ignored. The research adopts a normative juridical approach, examining primary legal materials (the 1945 Constitution and Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes) and secondary legal materials through literature studies and content analysis. The results show that the prevailing mediation framework tends to prioritize speed and formality, potentially giving rise to a "pseudo-consensus" that does not reflect workers' free will. The neutrality of the mediator that is mechanical in nature has failed to correct the imbalance of power in industrial relations. This study concludes that mediation should be repositioned as an integral part of the constitutional rights protection system, with the state playing an active role as guardian of social justice. Policy recommendations include strengthening technical guidelines for mediation in line with Pancasila values, training mediators to be oriented toward social justice, and encouraging the Constitutional Court to interpret labor norms progressively. The implications of this research theoretically enrich the construction of labor law of a constitutional nature, while making a practical contribution to the reform of national labor policies that are more in favor of the protection of vulnerable groups